A dois passos de Wakanda : uma proposta de uso do cinema com temática negra para o ensino de história - Santos, Jairton Peterson Rodrigues dos (2021)
The proposal of this article is to analyze the social representation of black people on the Black Panther movie (2018) aiming its use in Teaching History, since this topic dialogues to one of the premises of the Law of Directives and Bases of National Education (LDBE) n° 9.394/96, which has to do with the requirement of the Teaching of History and Afro-Brazilian and African Culture. This way, its examination makes possible working with ethnic-racial relations. The theoretical apparatus on the movies and its relation to History and the Teaching of History is based on Marc Ferro, Robert Rosenstone and Napolitano. The analysis of the movie was reasoned from the Cultural History and had as a pillar the Roger Chartier´s concept of social representation. We also elaborate on the contributions of Circe Bittencourt, Selva Guimarães and Thaís Nívea Fonseca. Also important for this article are the works of Paulo Freire and bell hooks. The research has a qualitative nature and brings the analysis of the movie as a possibility of using the cinema in order to promote discussions based on racial diversity questions and the empowerment. Through our own experience in the classroom and in bibliographical researches, we emphasized the cinema in the Teaching of History, specifically in the debate of the representation of the black people in the Basic Education. Starting there, we believe this article adds to the promotion of a shared reflection around the social representation of the black people, helping the work of the History teacher in the Basic Education, especially the Secondary School, in addition to elaborate a pedagogical strategy that enables the sociability of the results obtained from other educators interested in the mentioned topics. With the work finished, a didactical sequency is presented as a pedagogical instrument, with procedures for the analysis of the proposed movie and, as a crowning moment, an audiovisual production made by students entitled “My Wakanda”. This product intends to foment some knowledge that help teachers to encourage their students to understand and value their community, causing an education as a practice for freedom.